Application of CPM and PERT On Construction of Rail Tracks (International Journal of Innovative Research in Computer Science & Technology, 2022)
As a foundation for project planning,  execution, and supervision, management may use the  Project Evaluation and Review Technique (PERT) and the  Critical Route Method (CPM) to discover the longest time consuming, or consuming, path across a network of tasks  or activities. The solutions assist managers in maximizing  the shortest time period feasible in order to save project  costs and time in half. The use of project planning on the  construction of railway lines is shown in this study article,  which uses two project management methodologies. To  demonstrate the logical sequence of actions to be  undertaken in this research paper in order to fulfill this  article's purpose, I used the Project Evaluation and Review  Technique (PERT) and the Critical Path Method (CPM).  The benefits of utilizing CPM scheduling to build railway  tracks are discussed in this work. According to the results,  the construction may be completed in 852 days rather than  the 900 days initially projected, saving roughly 6%. This  will show up the network diagram together with beginning  and completion timings with the list of activities related  with the target in an effective method so as to accomplish  the building on or before a defined time limit with required  quality standard.
Keywords: Critical Path Method; Construction of Rail Track; Operation Research; Project Planning; Project Evaluation and Review Technique